A framework for regional high-level technical screening of promising CCUS value chains - Lothe, Ane Elisabet; Gravaud, Isaline; Ringstad, Cathrine; Silva, Eirik Falck da; Skagestad, Ragnhild; Shogenova, Alla; Shogenov, Kazbulat; Sousa, Leandro; Wójcicki, Adam; Sınayuç, Çağlar; Yıldırım, Betül; Bülbül, Sevtaç; et al. (Frontiers in Earth Science, 2025)
To support the European Green Deal and accelerate climate mitigation, the CCUS ZEN project conducted a high-level technical screening of Carbon Capture, Utilization, and Storage (CCUS) value chains in the Baltic and Mediterranean regions. These regions were chosen, since they have lower maturity levels for CCUS compared with the current development in the North Sea region. The study mapped industrial carbon dioxide (CO2) emission sources, potential storage sites, transport infrastructure, and utilization options. Emission clusters and hubs were identified based on volume, location, and industry type, while for each mapped storage site, information was gathered about the type of reservoir (deep saline aquifer or depleted hydrocarbon field), the onshore or offshore location, the capacity of the reservoir and the Storage Readiness Level, indicating the maturity of the capacity evaluation. Transport options included pipelines, shipping, and multimodal solutions were presented. This study defined unique high-level technical CCUS value chain screening workflow for mapping of emitters, infrastructures to storage screening. An open geographical information system was used for mapping the emitters and storage sites from previous reports, and to illustrate emission clusters and possible transport routes, both existing and future infrastructures. The screening revealed significant CO2 emission sources and storage capacities across the regions, with notable clusters in Poland, Germany, Italy, and Turkey. The Baltic region showed three times the storage capacity of the Mediterranean region. Eight promising CCUS value chains were defined, integrating source-sink matching and infrastructure feasibility. A detailed case study of Southern Italy and Greece was presented, to demonstrate the potential for regional CCUS deployment, highlighting challenges such as data availability, storage capacity uncertainty, transport possibilities and stakeholder coordination. This study will provide a foundation for further development and stakeholder engagement in CCUS planning across Europe.